From Home to Heart: Investigating the Mediating Role of Spirituality in the Relationship between Family Functioning and Character Strength - Ramadhani, Hetti (Universitas Ahmad Dahlan, 2025)
Previous studies have demonstrated that character strength significantly influences students’ future success, with the dimension of humanity being a central aspect of individual character. This study aimed to examine the relationship between family functioning and students’ character strengths, with spirituality serving as a mediating variable. Addressing a gap in existing literature, this research highlights the dual influence of environmental and internal factors in the development of character strength—whereas previous studies have predominantly focused on external determinants alone. A total of 317 junior high school students participated in the study by completing an online questionnaire. The instruments used included the Values in Action Inventory for Youth (VIA-Youth), the Aspects of Spirituality (ASP) Questionnaire, and the Family Assessment Device (FAD). Data were analyzed using JASP (Jeffrey’s Amazing Statistical Program). The findings revealed that spirituality significantly mediated the relationship between family functioning and character strength (β = 0.070, SE = 0.013, p < 0.001). Notably, the direct effect of family functioning on character strength (β = 0.158, SE = 0.023, p < 0.001) was lower than the total effect when the mediator was included (β = 0.228, SE = 0.024, p < 0.001). These findings underscore the importance of spirituality as an internal mechanism that promotes prosocial behavior and contributes to the development of students’ character strengths. Additionally, positive family functioning plays a foundational role in shaping students’ intrinsic values and moral dispositions. The implications of this study support efforts to strengthen human development policies and interventions aimed at fostering resilient and virtuous youth capable of adapting to future societal challenges.